Physical Dating Aggression and Proximal Changes in Psychosocial Symptoms in Young Adulthood - Collibee, Charlene (Journal of family violence, 2024)
Purpose: Physical dating aggression is prevalent within young adulthood, yet little is known about within-relationship effects of physical dating aggression on psychosocial adjustment. The present study uses an intensive longitudinal design to capture proximal changes (i.e., one month later, and across 6 months) in psychosocial adjustment following physical dating aggression. Methods: Between 2014 and 2016, data was collected in six monthly waves from 120 participants ages 18–25 (50% female, M age Wave 1 = 22.44; 10% African American, 17.5% Hispanic. 62.5% Caucasian). Results: Both immediate changes in the level of psychosocial adjustment and the growth trajectory of psychosocial adjustment were examined. Wave 1 physical dating aggression was associated with immediate changes in internalizing and trauma symptoms. Further, Wave 1 physical dating aggression predicted increased growth in both externalizing and internalizing symptoms. Conclusions: Findings highlight that psychological consequences of physical dating aggression may emerge quickly, with implications for potential increased risk for subsequent involvement in physical dating aggression.